New insights into evaluating catalyst activity and stability for oxygen evolution reactions in alkaline media. Issue 1 (13th November 2017) - Li, Guangfu; Anderson, Lawrence; Chen, Yanan; Pan, Mu; Abel Chuang, Po-Ya
Abstract : New insights into efficient oxygen evolution were obtained by developing robust evaluation protocols and understanding interfacial behaviors. Abstract : The growing development of oxygen-evolution-reaction (OER) catalysts has increased the demand for robust evaluation protocols to identify promising candidates. In this work, we successfully establish an effective experimental protocol to quantify the intrinsic performance of OER catalysts in a standard thin-film rotating-(ring)-disk-electrode system. Furthermore, a new insight into the electric double layer (EDL) microstructure is gained to illustrate all experimental observations in alkaline media. The results indicate that IrO2 has 2.6-times higher activity than NiCo2 O4, due to the improved reaction kinetics, charge transfer and O2 -transport occurring in the EDL. However, after 10 000 cycles of cyclic voltammetry (CV), NiCo2 O4 shows much higher stability due to continuous EDL structural modifications. In particular, it is revealed that the EDL charging process, accompanied by the electrocatalytic OER, has a strong effect on catalyst–electrolyte interfacial behaviors, which, in turn, determine the accuracy of electrochemical measurement results. It is further found that the electrochemical surface area (ECSA) obtained from traditional CV measured capacitance cannot accurately reflect the actual reaction sites of various catalysts during the OER. This discrepancy exists mainly because of the EDL capacitance, which is referred to as the inner capacitance caused by less accessible active sites. Alternatively, a novel method based on in situ electrochemical impedance spectroscopy has demonstrated improved accuracy in obtaining potential-dependent ECSAs, comparable to ex situ Brunauer–Emmett–Teller surface area measurements.